Diabetic Peripheral Neuropathy and Depression: Dancing with Wolves? - Mini-Review and Commentary on Alghafri et al. “Screening for depressive symptoms amongst patients with diabetic peripheral neuropathy” (The Review of Diabetic Studies, 2021)
The co-existence of diabetic peripheral neuropathy (DPN) and depression in subjects with diabetes is being increasingly recognized. The interaction of these two serious comorbidities may increase morbidity and mortality. An emerging thought is that persisting depression, along with stroke and cognitive dysfunction, may represent a cluster of potential microvascular injuries affecting the brain, which shares a common risk factor with DPN. Current evidence highlights metabolic and clinical covariates, which may interact in subjects with DPN and depression. However, there is a lack of rigorous enquiry into the confounding effect of cognitive dysfunction and vascular brain disease. Furthermore, high-quality longitudinal studies exploring the direct impact of these comorbidities on diabetes course and on the progression of the comorbidities themselves are lacking. Improved insights into comorbid DPN and depression may help to improve screening for and treatment of both these conditions.